An apparent new syndrome of extreme short stature, microcephaly, dysmorphic faces, intellectual disability, and a bone dysplasia of unknown etiology. Issue 7 (19th May 2020) - Stinson, Jennifer L.; Brault, Jennifer A.; Delk, Paula R.; Graham, Brett H.; Karmazyn, Boaz; Hall, Bryan; Weaver, David D.
Abstract: We report on a 26‐year‐old male with extreme short stature, microcephaly, macroglossia, other dysmorphic features, severe intellectual disability, and a bone dysplasia. The patient had an extensive genetic and biochemical evaluation that was all normal or noninformative. Recently, the proband died following a period of not eating. He likely had a previously undescribed syndrome of unknown etiology.